STATUS FITOFARMAKA DAN PERKEMBANGAN AGROTEKNOLOGI CABE JAWA (Piper Retrofractum Vahl.) - Rusdi Evizal (Universitas Lampung, 2013)
Java long pepper is a native of Southeast Asia, cultivated in Indonesia as spice and medicinal plant. As traditional medicine, its fruits are used as aphrodisiac, carminative, expectorant, laxative, digestive, anti-amoebic, anti-asthma, anti-septic and also have activity against several infection bacterial diseases. Recent clinical studies have reported that extract of java long pepper bean has androgenic effect and others pharmacological activity such as antioxidant, anti-cancer, and anti-diabetic. Java long pepper bean is commonly produced in the dryest land of Java dan Sumatera Island. The development of pharmacognosy of java long pepper and agrotechnology of cultivation in Indonesia was reviewed. Key words: Piper retrofractum, pharmacognosy, dry land, agro-technology